2016
DOI: 10.1371/journal.pone.0168320
|View full text |Cite
|
Sign up to set email alerts
|

LGR4 Is a Direct Target of MicroRNA-34a and Modulates the Proliferation and Migration of Retinal Pigment Epithelial ARPE-19 Cells

Abstract: The pathology of proliferative vitreoretinopathy and proliferative diabetic retinopathy is linked to proliferation, migration, and adhesion of the retinal pigment epithelium. MicroRNA-34a (miR-34a) expression modulates changes in proliferation and migration of retinal pigment epithelial cell line ARPE-19. In this study, we determined that miR-34a interacts with LGR4, identified by bioinformatics using TargetScan Human 5.0, to affect these changes. Double luciferase gene reporter assay confirmed miR-34a involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…29 We also showed that LGR4 is a direct target of miR-34a in RPE cells. 13 Here we showed that transfection of miR-34a to M17 and SP6.5 cells decreased…”
Section: Lgr4 Is Upregulated In Uveal Melanoma Cell Linesmentioning
confidence: 76%
See 2 more Smart Citations
“…29 We also showed that LGR4 is a direct target of miR-34a in RPE cells. 13 Here we showed that transfection of miR-34a to M17 and SP6.5 cells decreased…”
Section: Lgr4 Is Upregulated In Uveal Melanoma Cell Linesmentioning
confidence: 76%
“…One of the microRNAs of particular interest is microRNA-34a (miR-34a), which is a gene product from chromosomal locus 1p36.22 that is also a tumor suppressor in many types of tumor. [13][14][15] This has been implicated previously in normal biological processes such as cell proliferation, inhibition, cell cycle arrest, and senescence.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…TSC-mTOR pathway may result in the development of metabolic diseases and DM complications [37]. Curiously, the CDK6 gene was reported as an inductor of pancreatic β-cell replication and human islets proliferation by Fiaschi-taesch et al [38] The CDK6 is still suppressed indirectly by upregulation miRNAs in DM and complications of the disease [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…MiR 15 b and miR 16 show downregulation under hyperglycemic conditions and play a significant role in inhibiting insulin resistance and preventing the apoptosis under such conditions rendering protection to HRECs (68). In addition to their regulatory roles regarding insulin resistance, these mRNA also possess inhibitory roles in proinflammatory signaling hence preventing retinal leukostatis in DR that is illustrated by Ye et al Some inferences drawn by various conclusions state that proinflammatory signals such as IL-1β, TNFα and NFκB in HRECs cells under HG c o n d i t i o n s a r e s i g n i f i c a n t l y r e d u c e d b y overexpression of miR15 a and miR16 (69). Wang et al elucidated dual action of miR15 in DR that is antii n f l a m m a t o r y a n d a n t i a n g i o g e n i c ( 7 0 ) .…”
Section: Other Mirnas and Their Therapeutic Roles In Drmentioning
confidence: 99%